2013
DOI: 10.1155/2013/482167
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Acceptors and Additional Cationic Charges in Methylene Blue Derivatives: Photophysics and Antimicrobial Efficiency

Abstract: Photodynamic inactivation of bacteria (PIB) by efficient singlet oxygen photosensitizers might be a beneficial alternative to antibiotics in the struggle against multiresistant bacteria. Phenothiazinium dyes belong to the most prominent classes of such sensitizers due to their intense absorption in the red-light region (λ abs, max ca. 600–680 nm, ε > 50000 L mol−1 cm−1), their low toxicity, and their attachment/penetration abilities. Except simple substituents like alkyl or hydroxyalkyl residues, nearly no mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 62 publications
(57 reference statements)
2
52
0
Order By: Relevance
“…Methylene blue derivatives (structures are summarized in Table 2) such as new methylene blue, dimethyl methylene blue, and methylene green were developed with different functional substituents and shown to have improved effectiveness of killing bacteria. As indicated previously, increasing the positive charge on methylene blue correlated positively with increased APDT efficacy than native methylene blue [19,20], mainly because substitution with cationic functional groups improved the binding and uptake of the PS by bacteria relative to the parent structure [19][20][21]. For example, Felgentrager et al revealed that derivatization of methylene blue with tertiary ammonium substituents increased the uptake by microbial cells due to the fact that these substituents imposed a greater cationic charge in a pH-equilibrated aqueous solution, and therefore more avid bacterial cell binding, compared to primary or secondary substituents [19].…”
Section: Phenothiaziniumssupporting
confidence: 77%
See 2 more Smart Citations
“…Methylene blue derivatives (structures are summarized in Table 2) such as new methylene blue, dimethyl methylene blue, and methylene green were developed with different functional substituents and shown to have improved effectiveness of killing bacteria. As indicated previously, increasing the positive charge on methylene blue correlated positively with increased APDT efficacy than native methylene blue [19,20], mainly because substitution with cationic functional groups improved the binding and uptake of the PS by bacteria relative to the parent structure [19][20][21]. For example, Felgentrager et al revealed that derivatization of methylene blue with tertiary ammonium substituents increased the uptake by microbial cells due to the fact that these substituents imposed a greater cationic charge in a pH-equilibrated aqueous solution, and therefore more avid bacterial cell binding, compared to primary or secondary substituents [19].…”
Section: Phenothiaziniumssupporting
confidence: 77%
“…As indicated previously, increasing the positive charge on methylene blue correlated positively with increased APDT efficacy than native methylene blue [19,20], mainly because substitution with cationic functional groups improved the binding and uptake of the PS by bacteria relative to the parent structure [19][20][21]. For example, Felgentrager et al revealed that derivatization of methylene blue with tertiary ammonium substituents increased the uptake by microbial cells due to the fact that these substituents imposed a greater cationic charge in a pH-equilibrated aqueous solution, and therefore more avid bacterial cell binding, compared to primary or secondary substituents [19]. Furthermore, the tertiary ammonium-substituted methylene blue derivative possesses lower pK a values than the lower-order substituents, which results in faster deprotonation when bound to the negatively charged bacterial cell envelope structure and better uptake.…”
Section: Phenothiaziniumssupporting
confidence: 77%
See 1 more Smart Citation
“…Vilela et al (2012) did not observe any cytotoxic effect using 3000 M and 300 M of MG and MB, respectively, in the absence of light. Ergaieg and Seux (2009) used 3.65 M of MB and observed no inhibitory effect on cell viability in the dark, while Felgenträger et al (2013) reached the same conclusion using MB 100 M. Although all of the studies cited used the same standard E. coli strain (ATCC 25922), the results are different since other factors must be considered as conditions for cultivating bacteria, growth stage, PS solutions (in de-ionized water, saline or culture medium), contact time with the bacteria in PS in the dark, among other Rev.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore MB was substituted with methyl-groups (dimethyl methylene blue), ethyl-group (new methylene blue) or a nitro-group (methylene green) [38][39][40]. Felgentrager et al showed that additional cationic charges (primary, secondary and tertiary ammonium residues) in methylene blue derivatives (MB3 & MB4) lead to a better aPDI efficiency [41]. The aPDI efficacy of these MB derivatives was improved from primary to secondary to tertiary ammonium residues.…”
Section: Phenothiazinium Chromophorementioning
confidence: 99%